Laryngeal view and temperature measurements while using the perilaryngeal airway (Cobra‐PLUS™) in children. Issue 12 (25th September 2013) - Tan, Gee Mei; Galinkin, Jeffrey L.; Pan, Zhaoxing; Polaner, David M.
Summary: Introduction: The Cobra‐PLUS™ perilaryngeal airway (CP) is a modification of the Cobra perilaryngeal airway. It has a distal curve for easier placement and a thermistor on the pharyngeal cuff. We assessed the orientation of the larynx to the CP and compared temperatures measured using CP to temporal arterial (TA) and infrared tympanic (T) thermometers. Methodology: American Society of Anesthesiologists (ASA) physical status 1 and 2 children 0–18 years old undergoing general anesthesia using CP were grouped into different weight cohorts. A fiberoptic scope was inserted through the CP, and laryngeal views were recorded and graded off line. Temperatures were measured from the CP, TA, and T at 15‐min intervals for four readings or until the end of surgery. The CP was removed, while the patient was deeply anesthetized. Results: Eighty subjects were analyzed. 87.5% (cohort range 75–95%) had an unobstructed view of the larynx. No serious adverse effects noted. Three hundred and sixteen temperature data points were recorded for each measured site. CP temperatures were consistently lower than TA and T with a bias of 0.9 and 0.6°C, respectively. Using temperatures measured at time 0 and 15 min, CP was associated with a larger intraclass correlation coefficient and smaller repeatability coefficient when compared to TA or T (ICC 0.65, 0.46. 0.44 and RC 0.78, 1, 1.36, respectively), indicating it had a better measure and remeasure reliability. Conclusion: The CP has a better orientation to the larynx compared with its previous version. It may be used to reliably trend intraoperative temperatures.